In Search for Design Elements: A New Perspective for Employing Ethnography in Human-Computer Interaction Design Research. Issue 8 (9th May 2021) - Rapp, Amon
ABSTRACT: Design ethnography has been widely used in Human-Computer Interaction (HCI) to understand people's everyday behaviors, in order to build technologies capable of meeting users' needs. Building on top of the recent debate on ethnography within HCI, this article proposes to employ reflexivity and theoretical pluralism to ground a new way of using design ethnography in HCI, directly envisioning novel designs during the fieldwork. Inspired by design practices like biomimicry, I describe the figure of the ethno-designer, a digital design ethnographer who dives into 'successful' virtual environments in search for insightful design patterns, with the purpose of creating new designs in other, even distant, contexts. In this perspective, the fieldwork becomes an incessant source of inspiration for identifying effective 'design elements', understanding how they work and their 'experiential effects', and producing design implications to create novel technologies across multiple application domains.